2020
DOI: 10.1126/sciadv.aaw0870
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of service life of polymer electrolyte fuel cells through application of nanodispersed ionomer

Abstract: In polymer electrolyte fuel cells (PEFCs), protons from the anode are transferred to the cathode through the ionomer membrane. By impregnating the ionomer into the electrodes, proton pathways are extended and high proton transfer efficiency can be achieved. Because the impregnated ionomer mechanically binds the catalysts within the electrode, the ionomer is also called a binder. To yield good electrochemical performance, the binder should be homogeneously dispersed in the electrode and maintain stable interfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(33 citation statements)
references
References 36 publications
1
32
0
Order By: Relevance
“…For comparison, a PFSA–PTFE reinforced membrane without the use of any CeO x dispersions was also prepared and named as PFM. Finally, CeO x _A PFM and CeO x _B PFM were treated in 0.5 M H 2 SO 4 for 2 h and boiling deionized water for another 2 h (method II [ 22 , 30 , 31 , 32 , 33 , 34 ]). The acid treatment has been widely used to remove metallic cations existing in the membranes by exchanging the cations that participate in the ionic bonding with –SO 3 − groups in the PFSA matrices with protons, while the boiling water treatment was conducted to wash off excessive H 2 SO 4 molecules from the membranes.…”
Section: Methodsmentioning
confidence: 99%
“…For comparison, a PFSA–PTFE reinforced membrane without the use of any CeO x dispersions was also prepared and named as PFM. Finally, CeO x _A PFM and CeO x _B PFM were treated in 0.5 M H 2 SO 4 for 2 h and boiling deionized water for another 2 h (method II [ 22 , 30 , 31 , 32 , 33 , 34 ]). The acid treatment has been widely used to remove metallic cations existing in the membranes by exchanging the cations that participate in the ionic bonding with –SO 3 − groups in the PFSA matrices with protons, while the boiling water treatment was conducted to wash off excessive H 2 SO 4 molecules from the membranes.…”
Section: Methodsmentioning
confidence: 99%
“… 3 , 4 Thus, the effect of the ionomer fraction has been investigated to control its structure, 5 , 6 and previous studies have reported improved PEFC performances with an increase in the ionomer distribution homogeneity. 7 , 8 …”
Section: Introductionmentioning
confidence: 99%
“…A perfluorosulfonic acid ionomer (PFSA ionomer) consists of a polytetrafluoroethylene (PTFE) backbone having a chemically strong structure [ 12 ] and a perfluoro side chain containing a sulfonic acid group (-SO 3 H) at the end [ 13 ]. The perfluoro structure containing sulfonic acid induces a hydrophobic/hydrophilic microphase separation form for fast proton conduction [ 14 ].…”
Section: Introductionmentioning
confidence: 99%